Smart wattmeter - abotareef, Sameer; barakat, Mohamad (My University, 2018)
Growing concern about energy consumption is promoting the better usage of energy resources at different levels of human activities. It is a fact that the domestic sector has an increasing impact on world’s energy consumption. Despite continuous improvement efforts made by domestic equipment manufacturers, appliances such as refrigerators, space heating/cooling systems, water heaters, clothes washers, dryers, lighting and dishwashers continues to burden household energy bill. On the other hand, appliances based on non-linear loads are continually increasing with the mass production of electronically operated devices, so their impact on electricity energy consumption is tending to grow over the time. Power measurement is a very old and often discussed topic [9]. Professionals from the industry have identified and defined the many elementary methods frequently utilized in power meters. Such types of methods have been employed for decades in the current power meters. The circuit of a FM wireless remote switch presented here is very easy to build and can be used to toggle a load anywhere within a radial distance of 50 meters. The above system is controlled through a mini transmitter circuit operating at around 100MHz FM waves. The receiver or the controller board which is the main part of the circuit is actually a readymade FM radio kit, suitably modified for the purpose.